Surveillance Colonoscopy following Resection of Colorectal Polyps and Cancer - Douglas K Rex (Canadian Journal of Gastroenterology)
Patients undergoing clearing colonoscopy with resection of adenomas should generally have their next examination at three years. Exceptions include large sessile adenomas removed piecemeal (re-examine at two to six months until no evidence of recurrent polyp, then at one year), average risk patients with a single tubular adenoma (next examination at five years) and patients with 'numerous' adenomas (next examination at one or two years). Patients with surgically resected colorectal cancer should have a clearing colonoscopy preoperatively or within two to three months of surgery in obstructed patients, even if the preoperative barium enema is negative for proximal lesions. After the clearing colonoscopy, subsequent examinations can be performed based on the associated adenoma findings.